A Production systems study on USA Laboratories, Inc. - Balde, Bernard Roy; Liwanag, Michael P.; Ona, Victor Gabriel M.; Pasinio, Anna Katharina S.; Pineda, Michele C.; Pobre, Christian Quincy Q. (College of Engineering, 1996)
The study group conducted an Operations Management and a Quality Evaluation Audit on USA Laboratories Incorporated with an emphasis on the production of its Amoxicillin capsule line. Problems on the process of encapsulation is currently being experienced by the company. Product yield is not met and material wastage results. Their system on capacity and production planning is not well established. The company is considering sub-contracting the production of Amoxicillin capsules for its sister company USA generics. The volume in production is expected to increase with this and the present system is not capable of meeting this demand. The group has come up with an integrated solution methodology to the current problems. This includes the purchase of an automated encapsulating machine and a blister packaging machine, Automation of the encapsulation process would result in less defective products produced and a higher output level from 13,000 capsules per day to 130,000 capsules. The purchase of an automated blister packaging machine was also considered since and increase of volume would entail a faster packaging time for the product. This would also give a better assurance to the company with regard to the quality of the packed drugs since they can personally supervise the process. Total investment needed for these two machines is P 7.5 Million and economic life is expected to be 10 years. Economic evaluation resulted in a payback of 3.5 years, a profitability index of 1.5, an internal rate of return of 31% and a net present value of P 5 Million. The group also proposed a forecast based on the industry trend for pharmaceutical companies. The seasonal index for the sales of amoxicillin was used to compute for the forecasted demand. Capacity was also evaluated and was found out to be adequate for both manpower and machine requirements. Finally, a production plan was prepared for the year 1996-1997.